A Quantitative System Pharmacology Computer Model for Cognitive Deficits in Schizophrenia. (3rd April 2013) - Geerts, H; Roberts, P; Spiros, A
Abstract : Although the positive symptoms of schizophrenia are reasonably well‐controlled by current antipsychotics, cognitive impairment remains largely unaddressed. The Matrics initiative lays out a regulatory path forward and a number of targets have been tested in the clinic, so far without much success. To address this translational disconnect, we have developed a mechanism‐based humanized computer model of a relevant key cortical brain network with schizophrenia pathology involved with the maintenance aspect of working memory (WM). The model is calibrated using published clinical experiments on N‐back WM tests. We further simulate the opposite effect of γ‐aminobutyric acid (GABA) modulators lorazepam and flumazenil and of a published augmentation trial of clozapine with risperidone, illustrating the introduction of new targets and the capacity of predicting the effects of polypharmacy. This humanized approach allows for early prospective and quantitative assessment of cognitive outcome in a central nervous system (CNS) research and development project, thereby hopefully increasing the success rate of clinical trials. CPT: Pharmacometrics & Systems Pharmacology (2013) 2, e36; doi:10.1038/psp.2013.12 ; advance online publication 3 April 2013